2007
DOI: 10.1890/06-0750.1
|View full text |Cite
|
Sign up to set email alerts
|

Plant‐trait‐based Modeling Assessment of Ecosystem‐service Sensitivity to Land‐use Change

Abstract: Evidence is accumulating that the continued provision of essential ecosystem services is vulnerable to land-use change. Yet, we lack a strong scientific basis for this vulnerability as the processes that drive ecosystem-service delivery often remain unclear. In this paper, we use plant traits to assess ecosystem-service sensitivity to land-use change in subalpine grasslands. We use a trait-based plant classification (plant functional types, PFTs) in a landscape modeling platform to model community dynamics und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
105
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(108 citation statements)
references
References 57 publications
2
105
0
1
Order By: Relevance
“…We used a previously published data set depicting changes in FD and EP in subalpine grasslands under different combinations of past and present land use (24,40,41). Key ES of importance to regional stakeholders, including farmers, other local residents, and tourists, were related to grassland EP (Table 1) (41).…”
Section: Legend)mentioning
confidence: 99%
See 2 more Smart Citations
“…We used a previously published data set depicting changes in FD and EP in subalpine grasslands under different combinations of past and present land use (24,40,41). Key ES of importance to regional stakeholders, including farmers, other local residents, and tourists, were related to grassland EP (Table 1) (41).…”
Section: Legend)mentioning
confidence: 99%
“…Our case study illustrates the variety of ways in which EP underlying the delivery of ES can be related to abiotic factors and different components of FD. The quantitative models produced can also be applied to make projections of the future delivery of ES under contrasting land cover change scenarios (41). The links between CWM of plant traits and EP are strong and widespread, as shown by theory and accumulating empirical evidence under contrasting ecological and biogeographical contexts.…”
Section: Reducing Uncertainty In the Prediction Of Es Delivery In Resmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that changes in land use lead to changes in species composition, interactions between species and available ecosystem services (Quétier et al, 2007;Chemini & Rizzoli, 2014). The Alps do, in fact, provide a great number of ecosystem services: protection from natural hazards, CO 2 storage and accumulation in soil or biomass, provision of raw materials, provision of water, genetic diversity and tourism opportunities (Grêt-Regamey et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These semi-natural grasslands are of major importance for nature conservation as they often harbour a diverse flora and fauna containing rare species . However, these species assemblages are specifically adapted to management and therefore strongly endangered by changes in management (Quétier et al 2007). Since the beginning of the last century traditional land-use practices were often altered due to economical reasons since agriculture was intensified or sites were abandoned (Watkinson and Ormerod 2001;Poschlod and WallisDeVries 2002;Poschlod et al 2005).…”
Section: Introductionmentioning
confidence: 99%